PENGARUH PERTUMBUHAN EKONOMI TERHADAP KETIMPANGAN PEMBANGUNAN ANTAR KABUPATEN/KOTA DI PROVINSI SUMATERA UTARA TAHUN 2016-2020 - Hasan, Suhadi; M. Zahrin Piliang; Suci Mutia Sari Siregar (Sekolah Tinggi Ekonomi dan Bisnis Islam (STEBIS) Al-Ulum, 2023)
The purpose of this study was to determine: (1) economic growth between districts/cities in North Sumatra Province, (2) the level of inequality between districts/cities in North Sumatra Province, (3) the effect of economic growth on development inequality between districts/cities in the Province North Sumatra. This study uses secondary data from the Central Bureau of Statistics (BPS) for 2016-2020 using descriptive and regression analysis methods and the data used is panel data. Development inequality is calculated using the Williamson Index. The effect of economic growth on regional development inequality was analyzed using a random effect linear regression model. The results of the study concluded (1) economic growth between regencies/cities in North Sumatra Province in 2016-2020 experienced ups and downs even in 2020 economic growth greatly decreased drastically with an average economic growth of 4.13%, (2) Williamson Index values for all districts / cities in North Sumatra Province during 2016-2020 showed inequality in economic development at low criteria, (3) economic growth did not significantly affect development inequality in North Sumatra Province